Patient Protection for Operations Using Telesurgery Technology - Naya Puspita; Fransisca Lenny Prabandani; Elsya Crisnaysella Grejvania; Rethana Oktaria Puspitarani (Immortalis Journal of Interdisciplinary Studies, 2025)
This study aims to examine the legal and ethical protection mechanisms available topatients undergoing telesurgery—robotic surgical procedures conducted remotely viatelecommunication systems. Positioned within the emerging discourse on medical law indigital healthcare, this research addresses a critical regulatory gap as telesurgery becomesincreasingly globalized yet lacks adequate international legal instruments. Through aqualitative doctrinal approach using library research, this study synthesizes literaturefrom legal, ethical, and biomedical sources to explore five primary questions, includinginformed consent adequacy, cross-border regulatory barriers, and the distribution ofliability in system failures. The findings reveal that current legal systems in both developedand developing nations are not sufficiently equipped to guarantee patient safety and rightsin telesurgical contexts. Notably, the absence of cross-jurisdictional regulations, coupledwith limited public understanding of technological risks, contributes to systemicvulnerability. The study offers a novel contribution by proposing a multi-layeredregulatory framework integrating national health law, international medical ethics, andprivate-sector accountability. This integrative model ensures that telesurgery evolves asnot only a technological innovation but also a legally and ethically responsible medicalpractice